1994
DOI: 10.1086/646830
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Nosocomial Infection: A Contemporary Perspective

Abstract: The history of airborne nosocomial infections is reviewed, and current beliefs about such infections are placed into their historical context. Possible sources, both animate and inanimate, of airborne nosocomial infections in the hospital environment are identified. Viruses, bacteria, and fungi that have been important causes of airborne nosocomial infections in the past are discussed, and examples of key studies that have confirmed an airborne route of transmission are presented. Where relevant, measures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 38 publications
0
24
0
5
Order By: Relevance
“…Transmission through injuries with contaminated devices and direct contact with tissue and contaminated fluids has been reported for bacterial agents such as Staphylococcus aureus [10] and viral agents like hepatitis B and C [4,5]. Transmission of organisms having an airborne phase in their route of dissemination has also been reported [1,11], with evidence for such transmissions of Mycobacterium tuberculosis, methicillin-resistant Staphylococcus aureus, legionella, varicella-zoster, smallpox and influenza [2,4,9]. It can be concluded that there is a risk for health care workers in the operating room present during surgeries where aerosols are produced through highspeed milling or cutting devices.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission through injuries with contaminated devices and direct contact with tissue and contaminated fluids has been reported for bacterial agents such as Staphylococcus aureus [10] and viral agents like hepatitis B and C [4,5]. Transmission of organisms having an airborne phase in their route of dissemination has also been reported [1,11], with evidence for such transmissions of Mycobacterium tuberculosis, methicillin-resistant Staphylococcus aureus, legionella, varicella-zoster, smallpox and influenza [2,4,9]. It can be concluded that there is a risk for health care workers in the operating room present during surgeries where aerosols are produced through highspeed milling or cutting devices.…”
Section: Discussionmentioning
confidence: 99%
“…Second, most of the culturable particles collected in these ambient outdoor samples were probably fungal spores. Fungal spores, particularly Aspergillus spp., are important sources of airborne nosocomial infections during construction and renovation in and near healthcare facilities (Eickhoff, 1994). However, in healthcare settings and buildings with increased risk of biological attack, bacterial and viral particles may be of even greater concern.…”
Section: Discussionmentioning
confidence: 99%
“…Although current infection control practices emphasize contact as the major mechanism for the spread of nosocomial infections, there continues to be an ongoing interest in airborne sources of infection in the hospital environment. These are primarily related to the spread of multidrug‐resistant tuberculosis, aerosol spread of saprophytic fungi in the transplant population, and the potential spread of multidrug‐resistant microorganisms in heath care facilities 11 …”
Section: Discussionmentioning
confidence: 99%